Realist methodologies informing the development, implementation, and scale-up of complex socio-medical interventions: A scoping review protocol - Md Koushik Ahmed; Alejandro Argüelles Bullón; Babatope O Adebiyi; Crystal Polanco Serra; Roslyn Copeland; Ferdinand C. Mukumbang (PLoS ONE, 2026)
Background Understanding how and why complex socio-medical interventions work across diverse settings is essential for addressing health inequities. Realist methodologies, grounded in realism, provide a framework to explain what works, for whom, in what contexts, and why by focusing on generative mechanisms and contextual conditions. While realist approaches have been extensively applied in implementation science, it is unclear to what extent they have been applied across the development, implementation, and scale-up phases of interventions. This scoping review aims to map how realist methodologies have been applied to inform the lifecycle of complex socio-medical interventions. Methods We plan to follow the framework of Arksey and O’Malley and the Joanna Briggs Institute (JBI) as well as PRISMA-ScR guidelines, to map how realist methodologies have been applied to inform the lifecycle of complex socio-medical interventions. Four databases (PubMed, Web of Science, CINAHL, and PsycINFO) will be searched, supplemented by grey literature and citation tracking. Two reviewers will independently screen peer-reviewed, English and Spanish-language, realist-informed studies. We will chart data on study characteristics, intervention details, realist findings (e.g., Context-Mechanism-Outcomes, programme theories), and methodological insights. We will include descriptive, thematic, and narrative synthesis, as well as network visualization. The protocol is registered in open science framework (OSF) registries ( https://osf.io/t8z2b/overview ). Discussion We expect to identify how realist inquiry contributes to building explanatory programme theories that guide the development, implementation, and scale-up/adaptation of complex socio-medical interventions. This review will offer practical insights for implementation scientists and healthcare practitioners on how and why complex health interventions work and can be adapted for successful implementation. Understanding the adoption of realist methodologies across the intervention lifecycle will enhance the design, implementation, and effective scale-up of socio-medical interventions in complex settings.